CD248+ Cancer-Associated Fibroblasts: A Novel Prognostic and Therapeutic Target for Renal Cell Carcinoma - Xu, Chao; Zhang, Keying; Yang, Fa; Zhou, Xiang; Liu, Shaojie; Li, Yu; Ma, Shanjin; Zhao, Xiaolong; Lu, Tong; Lu, Shiqi; Zhang, JiaYu; Li, Hongji; et al. (Frontiers in Oncology, 2021)
Background: Tumor microenvironment (TME) play important role in renal cell carcinoma (RCC) progression. Cancer-associated fibroblasts (CAFs) regarded as the major part of TME participate in various tumor-promoting molecular events. Whereas, CAFs-mediated tumor progression and potential mechanism are largely unknown in RCC patients. Previously, we confirmed that CD248 is a promising biomarker of CAFs, which may provide insights to explore CAFs-based tumor-promoting effects. Methods: Expression profiling and clinical data of RCC patients were obtained from The Cancer Genome Atlas (TCGA) database. MCP-counter algorithm and Kaplan-Meier survival analysis were performed to explore the prognostic value of CAFs and CD248, respectively. Pearson correlation coefficient test and Student’s t-test were employed to evaluate the relationship between immunosuppressive TME and CD248 or CAFs. Immunochemical and immunofluorescence staining was performed to confirm the expression of CD248 within CAFs. CD248-specific siRNA was adopted to investigate its potential function in CAFs tumor promotion. Differentially expressed genes (DEGs), weighted gene co-expression network analysis (WGCNA), and enrichment analysis were conducted to clarify the function of CD248+ CAFs in RCC progression and its potential regulatory mechanism. Results: CD248 over-expression and CAFs infiltration could predict poor RCC prognosis, which might involve with immunosuppressive TME. CD248 could serve as a promising CAFs biomarker, and involve with tumor-promoting effect of CAFs. CD248+ CAFs infiltration might contribute to RCC progression and immunosuppressive TME through cell-extracellular matrix (ECM) interaction and metabolism regulation. Conclusion: CD248+ CAFs participated in the regulation of RCC progression and immunosuppressive TME, which might be a novel prognostic and therapeutic target for RCC.